Principles of swimming propulsion and issues of teaching: Using practical experiments to enhance understanding of lift principle and Magnus-effect - Strass, D.; Bäurle, W. (Biomechanics and Medicine in Swimming VIII, 1999)
Es werden einfache physikalische Experimente zum besseren Verständnis der physikalischen Grundlagen des Vortriebs, des dynamischen Auftriebs und des Magnus-Effekts vorgestellt.